2005
DOI: 10.1121/1.1830673
|View full text |Cite
|
Sign up to set email alerts
|

Ambient noise cross correlation in free space: Theoretical approach

Abstract: It has been experimentally demonstrated that the Green's function between two points could be recovered using the cross-correlation function of the ambient noise measured at these two points. This paper investigates the theory behind this result in the simple case of a homogeneous medium with attenuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
306
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 377 publications
(327 citation statements)
references
References 10 publications
17
306
0
4
Order By: Relevance
“…Afterwards, different theoretical approaches have formalised the link between correlation of random diffuse fields and Green's function retrieval Lobkis and Weaver, 2001;Derode et al, 2003a,b;van Tiggelen, 2003;Wapenaar, 2004;Snieder, 2004;Roux et al, 2005). The crosscorrelation technique has been used successfully in many applications in helioseismology (Duvall et al, 1993;Gilles et al, 1997), acoustics Lobkis and Weaver, 2001;Larose et al, 2004), oceanography (Roux and Kuperman, 2004;Sabra et al, 2005c), active seismic experiments (Bakulin and Calvert, 2006;Mehta et al, 2007) and seismology with the correlation of seismic coda (Campillo and Paul, 2003) or seismic noise (Shapiro and Campillo, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, different theoretical approaches have formalised the link between correlation of random diffuse fields and Green's function retrieval Lobkis and Weaver, 2001;Derode et al, 2003a,b;van Tiggelen, 2003;Wapenaar, 2004;Snieder, 2004;Roux et al, 2005). The crosscorrelation technique has been used successfully in many applications in helioseismology (Duvall et al, 1993;Gilles et al, 1997), acoustics Lobkis and Weaver, 2001;Larose et al, 2004), oceanography (Roux and Kuperman, 2004;Sabra et al, 2005c), active seismic experiments (Bakulin and Calvert, 2006;Mehta et al, 2007) and seismology with the correlation of seismic coda (Campillo and Paul, 2003) or seismic noise (Shapiro and Campillo, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 2009Li et al , 2010aYao et al 2008;Zheng et al 2008). The theoretical work and applications of ANT have been published by Campillo and Paul (2003), Weaver and Lobkis (2004), Weaver (2005), Shapiro and Campillo (2004), Shapiro et al (2005), Roux et al (2005) and Sabra et al (2005). Although this method has been applied in the areas involved in our study area, the results only obtain local linear crustal velocity structures (Cheng et al 2011) or reflect major overall structures (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Using correlational forms of the reciprocity theorems, Wapenaar & Fokemma (2006) showed how inter-receiver Green's functions could be constructed by crosscorrelating recorded fields whereas other studies have also revealed the limitations of that method (Snieder 2004;Roux et al 2005;Gouédard et al 2008). For obtaining a diffuse field Halliday & Curtis (2008) analyse the requirements in terms of source distribution for the retrieval of scattered surface waves.…”
Section: Introductionmentioning
confidence: 99%